Interpreting normalized and nonnormalized data after acute static stretching in athletes and nonathletes - Evetovich, T. K.; Cain, R. M.; Hinnerichs, K. R.; Engebretsen, B. J.; Conley, S. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to determine the effect of acute static stretching on torque and electromyography (EMG) in female athletes (ATHs) and nonathletes (NONATHs) using both normalized (NORM) and nonnormalized (NONNORM) data. Fifteen ATHs recruited from women's National Collegiate Athletic Association Division II varsity basketball and volleyball teams were paired to 14 NONATHs. Electromyography (µV) was detected over the rectus femoris during isokinetic leg extensions at 60 and 300°/s before (PRE) and after (POST) static stretching. There was a significant main effect for torque (mean ± SD PRE = 81.9 ± 22.7 Nm; POST = 77.0 ± 21.9 Nm) and EMG amplitude (PRE = 767.6 ± 288.6 µV; POST = 664.2 ± 219.3 µV) for PRE compared to POST. For the NORM data, there was a significant decrease in torque for the NONATHs (mean ± SD PRE = 73 ± 12 N·m; POST = 67 ± 12 Nm) but no significant difference for the ATHs (mean ± SD PRE = 65 ± 11 Nm; POST = 66 ± 8 Nm). The NONNORM data indicated that both the ATHs and NONATHs displayed a stretching-induced decrease in torque that may be manifested in a decreased ability to activate the muscle. The NORM data revealed the NONATHs but not the ATHs were hindered in their ability to produce torque as a result of the stretching. Coaches and ATHs may want to carefully consider whether to include stretching in their precompetition routine. When reading the literature, the practitioner should consider the manner in which the data were calculated and analyzed (NORM or NONNORM) because it may affect the conclusions of the study.